Novel Approach for Noise Removal of Brain Tumor MRI Images - Dhanuskodi, Anithadevi; Perumal, K. (British Journal of Healthcare and Medical Research, 2015)
In Image processing, Image denoising becomes mandatory for many applications. In medical imaging, An MRI (Magnetic Resonance Imaging) image provides high quality when estimated with CT imaging techniques and hence it is best suited for diagnosis. Even though it’s providing high quality informations, images may corrupted by noise due to acquisition and transmission. Noises have to remove while the mean time there is no loss of information and also have the capability to preserve edges. This paper presents a novel approach for denoise the brain tumor MRI images using combine features of Stationary Wavelet Transform (SWT), median filter and sharpening filter. Accordingly, this approach is intended to develop for the noise removal with the edge preserving qualities in brain tumor MRI images. In Wavelet, SWT shows a superior performance in denoising because of its multi-resolution property and no signal leakage. Median filter helps in preserving edges and edges are enhanced by sharpen filter .And the results are compared using some image quality factors to find out the similarity with the original images.